Hyperacute Cytokine Kinetics and Early Interleukin-10 Elevation as Predictors of Neurological Outcome in Post-Cardiac Arrest Syndrome - Jea Hun Oh; Hyo Joon Kim; Kyung Man Cha; Daehee Kim; Kiwook Kim; In Soo Kim; Ji Hoon Kim; Chun Song Youn; Sang Hoon Oh; Hyo Jin Bang; Ae Kyung Gong; Ji Sook Lee (Journal of Clinical Medicine, 2026)
Background: Post-cardiac arrest syndrome (PCAS) involves a complex interplay between systemic inflammatory and compensatory anti-inflammatory responses. The hyperacute kinetics of these cytokines and their incremental prognostic value beyond established brain injury biomarkers remain inadequately characterized. We aimed to evaluate whether the 6 h post–return-of-spontaneous-circulation (ROSC) cytokine profile predicts neurological outcome, with the Th1/Th2 ratio largely reflecting the IL-10 signal. Methods: This retrospective analysis of prospectively collected data from a single-center cardiac arrest registry included 56 cardiac arrest survivors (40 out-of-hospital, 16 in-hospital) treated with targeted temperature management (TTM) at 33 °C or 36 °C between January 2024 and December 2025. Serum IL-6, IL-10, IFN-γ (interferon-γ), and TNF-α (tumor necrosis factor-α) were measured at five time points (initial presentation (INIT), and 6, 24, 48, and 72 h post-ROSC). Neurological outcome was assessed using the Cerebral Performance Category (CPC) scale at 6 months after cardiac arrest, with poor outcome defined as CPC 3–5. Results: Eighteen patients (32.1%) had a good outcome (CPC 1–2) and 38 (67.9%) had a poor outcome at 6 months after cardiac arrest. Among the 38 poor-outcome patients, 2 were classified as CPC 3, 8 as CPC 4, and 28 as CPC 5 (death) at 6 months; the 6-month outcome was available for all 56 patients, with no loss to follow-up. Patients with poor outcomes exhibited a synchronized surge of IL-6 and IL-10 peaking at 6 h post-ROSC. IL-10 at 6 h showed the highest discriminative power among cytokines (area under the curve (AUC) 0.844) compared with IL-6 (AUC 0.761). Multivariable analysis using Youden-derived cut-offs revealed that IL-10 ≥ 154.32 pg/mL (adjusted odds ratio (aOR) 15.28, 95% CI 2.02–115.38, p = 0.008) and a Th1/Th2 ratio ≥ 0.0314 (aOR 0.09, 95% CI 0.01–0.61, p = 0.013) were independently associated with neurological outcome after adjustment for age and initial shockable rhythm. Conclusions: The 6 h post-ROSC window is a critical inflection point for immune dysregulation in PCAS. Early IL-10 elevation and collapse of the Th1/Th2 balance are independently associated with poor neurological recovery and add incremental prognostic information to established brain injury biomarkers. External validation in larger prospective cohorts is required.